2014
DOI: 10.1387/ijdb.140053st
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and its role in the trophoblast cell lineage

Abstract: DNA methylation functions as cellular memory beyond generations of cells and is involved in many biological processes. Because of its relatively stable nature compared with the transcriptome, the DNA methylation profile of cells can also be used to evaluate developmental similarity and cellular phenotypes. Recent insights into 5-hydroxymethylcytosine have started to reshape our view of the epigenetic regulation of mammalian development. Both global DNA methylation and hydroxymethylation levels change dynamical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…DNA methylation has been the most studied epigenetic modification and is associated to gene silencing when occurring in the promoter region of genes [8]. This epigenetic mark usually occurs in CpG dinucleotides and consists in the addition of a methyl group from the S-adenosylmethionine donor (SAM) to the fifth carbon of a cytosine, originating a 5-methylcytosine (5-mC) [9,10]. The enzymes that catalyze DNA methylation are well characterized and are designated DNA methyltransferases (DNMTs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation has been the most studied epigenetic modification and is associated to gene silencing when occurring in the promoter region of genes [8]. This epigenetic mark usually occurs in CpG dinucleotides and consists in the addition of a methyl group from the S-adenosylmethionine donor (SAM) to the fifth carbon of a cytosine, originating a 5-methylcytosine (5-mC) [9,10]. The enzymes that catalyze DNA methylation are well characterized and are designated DNA methyltransferases (DNMTs).…”
Section: Introductionmentioning
confidence: 99%
“…The enzymes that catalyze DNA methylation are well characterized and are designated DNA methyltransferases (DNMTs). Within this family, three enzymatically active types are identified, the maintenance methyltransferase DNMT1 and the de novo methyltransferases, DNMT3A and DNMT3B [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, H4 neither displays sequence divergence nor has any identified variants 14 , 15 . High-order chromatin organization in mammals is modulated by several epigenetic mechanisms, including DNA methylation and histone post-translational modifications 18 – 20 . Since there is a wide variety of histones, chromatin structure might change by changing the combination of histones.…”
Section: Introductionmentioning
confidence: 99%
“…Trophoblast methylation/demethylation is a major mechanism for differentiation and development. Although it is generally accepted that the methylation process is inhibitory during preimplantation embryonic development, it has been recently shown that active demethylation processes occur after implantation (10,11). Deregulation of the demethylation process could cause pregnancy-related diseases like PE.…”
mentioning
confidence: 99%